HR Management Strategy in Overcoming Conflicts Due to Differences of Opinion Between Bank Sumut Employees Using the OGSM Method - Sy Haura Munawwarah; Azhari Akmal Tarigan; Budi Dharma (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Common conflicts are faced by large organizations such as Bank Sumut, especially those arising from differences of opinion between employees, namely conflicts that are not managed properly can reduce productivity, lower employee morale, and create a disharmonious work atmosphere. This study was conducted at Bank Sumut with the type of research conducted being field research with a qualitative approach. With data collection through interview techniques on the head of HR at Bank Sumut as a solution to the problem. This study aims to explore and apply Human Resource (HR) management strategies in overcoming conflicts through the OGSM method (Objectives, Goals, Strategies, Measures). The OGSM method is used as a framework for setting goals, objectives, strategies, and measures of success in managing conflict. The main objective of implementing this method is to increase harmony and productivity in the Bank Sumut work environment. from this study is that the OGSM method is an effective tool in conflict management, able to create a more harmonious and productive work environment at Bank Sumut. These findings can be a guide for other organizations in managing conflicts due to differences of opinion in the workplace.